The Payment System Used by Auxilio Emergencial : Introduction of the Digital Social Account, and the Banking of More than 100 Million People in 9 Months - Lara de Arruda, Pedro (World Bank, Brasilia, 2022)
The auxilio emergencial (AE) was the main social policy in response to the Coronavirus disease 2019 (COVID-19) crisis in Brazil, and one of the most vigorous in the world, both in terms of its generosity, speed, and coverage, as well as because of the program’s auspicious design. The AE payment system combined Caixa’s historical experience, responsible for operating the payment of social transfers such as Bolsa Familia, with innovative solutions. These allowed the use of a 100 percent digital means of payment and with an incentive to save, which contributed to the largest collection of savings in the Brazilian historical series. AE utilized three entry channels: (a) automatic selection of Programa Bolsa Família (PBF) beneficiaries who will be eligible to receive more significant benefits through the AE program; (b) the automatic selection of people registered in the largest administrative registry of Brazilian social programs but who were not beneficiaries of the PBF; (c) passive selection based on requests submitted through the app developed by CAIXA for this purpose, which led to the creation of a new temporary registry (the ExtraCad). The AE was created to be a temporary program, with an expected duration of only three months. However, the benefit was reissued in 3 versions (each with its legal diploma) which share the same operational structure, although they maintain significant differences in their rules and procedures.